Painting and Irony - Herrera Ruiz de Eguino, Naiara (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2018)
Painting and irony, both move in an open and oscillating significance plane, both invite us to reconsider what surrounds us, to reread through an introspective reflection. Painting offers a set of realities where irony moves with total naturalness, whereas knowing the characteristics of irony allows approaching the interpretation of the pictorial works from a more critical and reflexive perspective. This way, the painting turns out to be an ideal form for the irony to take place, and the irony is a specially interesting discursive strategy for the interpretation of the pictorial works.